MANAJEMEN KARIR PADA WANITA : KOMPETENSI DAN POLITIK ORGANISASIONAL - Hartarini, Yovita Mumpuni; Ignatius Hari Santoso (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to examine differences in perceptions of the use oforganizational politics on career development. The sample used in this study were97 respondents in Semarang and Jakarta. This study uses the Kruskal Wallis 1Sample method with a significance level of 0.05. The results showed that there wasno significant difference between female workers regarding the use oforganizational politics in career development. Almost all agreed to useorganizational politics at some point to improve their performance and career. Themanagerial implication of the results of this research is that there is still a need forthe application of organizational politics for women workers to improve theircareers, not solely relying on their professional competence.